2E.002 Cycle of violence: childhood abuse and risk of violence revictimisation in adulthood. (14th March 2021) - Bellis, Mark A; Butler, Nadia; Quigg, Zara
Abstract : Interpersonal violence is a serious threat to the attainment of the Sustainable Development Goals (SDGs). A public health approach to violence prevention is crucial, and addressing risk factors is a key priority. Global research has demonstrated that childhood adversity increases risk of a range of poor outcomes across the lifecourse. This study used data from a nationally representative survey of household residents (n=21, 845), to examine the impact of childhood abuse (physical, sexual and psychological abuse, and witnessing domestic violence) on risk of adulthood violence revictimisation (physical assault (PA), intimate partner violence (IPV), and sexual violence (SV)). Compared to individuals who experienced no child abuse, those who experienced one type were, twice as likely to experience PA, and three times as likely to have experienced IPV and/or SV. Individuals who experienced multiple types were three, six and seven times more likely to experience PA, IPV, and SV, respectively. After controlling for the number of types experienced, associated types differed by adult violence outcome; child psychological and physical abuse were associated with IPV; psychological and sexual abuse with SV; and psychological abuse with PA. Findings from the study will be presented with consideration of strategies to prevent and respond to child abuse and the potential downstream effect on preventing interpersonal violence across the lifecourse and achieving the SDGs. With adulthood victimisation likely to compound the already detrimental effects of childhood abuse, and given that many associated outcomes represent adversities for the next generation, breaking the cycle of violence represents a critical priority.